Positive Affirmations Affected the Postpartum Blues Mental Health - Nasokha, Fauzul Munah; Noviana, Ekki; Dari, Wulan (STIKes Patria Husada Blitar, 2024)
Indonesia is currently being hit by the Covid-19 virus, while the incidence of postpartum blues is increasing, one of the influencing factors is the decline in mental health and perceived social support. The objetive of the research was to prove the effect of positive affirmations on mental health, perceived social support for postpartum blues mothers. This was analytic research with true experimental method, with randomized controlled, pretest-posttest design with control group. The number of samples was 40 respondents; 20 intervention respondents and 20 control respondents. The intervention group was given positive affirmation videos for 10 minutes, 5 times every day. The data obtained from the questionnaire. The analysis used to assess the variables was a paired sample test. To assess the differences in the two groups using the Independent T-test. The result showed the improvement in mental health before the intervention was 28.3 this value included weight. After the intervention was given, it was 13.3 in the normal category. The increase in perceived social support, before the intervention was given, was 24.7 the value was included in the low category, after being given the intervention, it was 38.4 in the medium category. The p-value before and after the positive affirmation technique treatment has a p-value <0.05, so there is a difference after being given positive affirmations, namely increasing mental health and perceived social support. Giving positive affirmations can improve mental health and perceived social support in postpartum blues mothers.